2013
DOI: 10.1097/mao.0b013e318295313c
|View full text |Cite
|
Sign up to set email alerts
|

Head Impulse Test Abnormalities and Influence on Gait Speed and Falls in Older Individuals

Abstract: Objective: To assess the prevalence of vestibular dysfunction in older adults using the head impulse test (HIT) and to assess the independent influence of HIT abnormalities on gait speed and fall risk in older individuals. Study Design: Cross-sectional study. Setting: Tertiary care academic medical center. Patients: Fifty community-dwelling individuals age 70 and older. Interventions: HIT (abnormal HIT defined as right or left HIT abnormality), visual acuity, monofilament testing, and grip strength. Main Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 37 publications
1
60
0
2
Order By: Relevance
“…While previous studies have collected VEMP data in aging populations(22), these data have not been linked to gait function. Studies that have evaluated the influence of vestibular function on gait have largely focused on tests of semicircular function such as head-impulse testing(24) or head-shake tests(8). Our analysis suggests that age-related changes in otolith function influence gait speed, and that these associations differ between men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies have collected VEMP data in aging populations(22), these data have not been linked to gait function. Studies that have evaluated the influence of vestibular function on gait have largely focused on tests of semicircular function such as head-impulse testing(24) or head-shake tests(8). Our analysis suggests that age-related changes in otolith function influence gait speed, and that these associations differ between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that head impulse testing, when used to screen for semi-circular canal function in older individuals, predicted slower gait speeds and increased fall risk(24). Yet the impact of the otolith organs in age-related vestibular loss and functional gait parameters has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A recent pilot study administered the HIT in a cohort of 50 healthy older adults to evaluate the prevalence of age-related vestibular loss in the community. The study observed a 50% prevalence of HIT abnormality, which was significantly associated with slow gait speed and fall risk (3). …”
mentioning
confidence: 99%
“…Indeed, we observed in prior work that older adults with impaired semicircular canal function had slower gait relative to adults with intact function. 23 We also previously reported an association between saccular dysfunction and slower walking speed among older women, but not older men. 24 The peripheral vestibular system senses head movements and responds to high-frequency head oscillations that occur during walking.…”
Section: Discussionmentioning
confidence: 59%